Hidden harvest: U.S. benefits from international research aid - Pardey, Philip G.; Alston, Julian M.; Christian, Jason E.; Fan, Shenggen (International Food Policy Research Institute, 1996)
This IFPRI Food Policy Statement compares the investment made by the U.S. Agency for International Development in CGIAR research with the contributions that investment has made to U.S. farm production. Using wheat and rice to illustrate the gains from international research on important food crops, the study measures the costs and benefits to the United States of research conducted by the CGIAR's International Maize and Wheat Improvement Center (CIMMYT) in Mexico and International Rice Research Institute (IRRI) in the Philippines and shows that past taxpayer contributions to the CGIAR have been repaid many times over.